Interaction of Culture and Entry Mode Strategy: The Malaysian Perspective - Singh, Amritpal (2003)
Previous studies undertaken in determining the relationship between national cultural distance and entry mode selection decisions by multinational corporations (MNCs) in the context of Foreign Direct Investments (FDI) has produced conflicting results. Numerous studies, undertaken in the field of international business strategy have drawn differing conclusions, with some showing culture distance has strong impact on the selection of wholly owned subsidiary or joint ventures, while some claim existence of no significant relationship. While many researches taking the challenge in coming forward to solve this paradox, the study undertaken by the Brouthers brothers, namely Keith and Lance Brouthers in their paper Explaining the National Cultural Distance Paradox has seen to take centre stage in solving this issue. The principles, and the findings, regarded as a breakthrough of all sorts is replicated to the study of the FDI scene in Malaysia. Looking at the behaviour of MNCs, this study focuses to answer is there any existence of culture on the trends of entry mode practiced by investing MNCs from 1995 to 2002, touching eight industries. Hofstede’s culture distance indices are used in this study. Next, for the observed periods, the study looks at how industry attributes and characteristics attract a particular mode of entry among firms. Underlying specific attributes at firm levels and industry levels are mentioned. In addition, a study is also undertaken to see trends and the preferred behaviour in selecting mode of entry by corporations based on nationality and geographical origin. The analysis covers periods split accordingly from pre and post financial crisis periods. There is a distinction noted in the preferred selection based on firm origin nationality during the observed periods. Reasons are forwarded on the behaviour with linking the findings to the previous studies undertaken. Both empirical and theoretical evidence is used to explore in providing to explain inference on the selection choices of entry modes in the Malaysian FDI context. On the whole, it’s concluded that culture besides other micro and macro factors do play a role in businessdecision-making where entry mode is concern, despite statistical findings proving otherwise.